Counseling on Building the Concept of a Sakinah, Mawaddah, and Warahmah Family for the Congregation of Basyirul Amin Prayer Room, Kulim Subdistrict, Kulim District - Adriani A; Alfahrezi Irfanda Fatih; Ahmad Haedar Ali; Maysarah M (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The dream of every married couple is to build a family life that is peaceful, secure, and filled with love. However, in reality, many unexpected problems arise when two people who love each other begin their married life. Shortly after marriage, conflicts and disputes may occur due to minor issues and various other factors, one of which is economic problems. Through this counseling activity, knowledge is provided to the congregation of Basyirul Amin Prayer Room—whose members are predominantly Muslim—regarding how to build the concept of a sakinah, mawaddah, wa rahmah (peaceful, loving, and compassionate) family. It is hoped that households can be managed in accordance with these ideals. Although minor conflicts cannot always be avoided, they can be controlled when individuals understand the fundamental principles of marital harmony. The Basyirul Amin congregation lives in an environment surrounded by oil palm plantations and industrial factory areas. Therefore, it is considered necessary to provide counseling and socialization so that if domestic issues arise within their community, they can be properly addressed with the support of local village authorities.